The effect of marketing strategies on firm performance: a study of furniture manufacturing SMEs in Johor Malaysia - Akbar, Fazal (2017)
Marketing strategies are critical to improve the performance of any small and medium-sized business in the world. The purpose of this study is to investigate the importance of marketing strategies for small and medium-sized enterprises in Johor, Malaysia, by focusing on the impact of different marketing strategies on firm performance. This thesis emphases on the views of managers and owners on marketing strategies and their impact on firm performance in furniture manufacturing SMEs. The researcher test a model that reflects the expected relationship between entrepreneurial, guerrilla, relationship, ambush, viral and niche marketing strategies and firm performance. Based on a review of pertinent literature, this thesis develops a model that reflects relationship between entrepreneurial, guerrilla, relationship, ambush, viral and niche marketing strategies and firm performance. Quantitative research approach using survey design was adopted. Data was collected using close-ended questionnaires systematically distributed to a sample of 250 potential managers and owners out of which 145 were received useful for the analysis. Both descriptive and inferential statistical tools such as factor analysis and Partial Least Square-Structural Equation Modeling (PLS-SEM) were used to analyse the data using SPSS 23 and SmartPLS 3 software. The study found that the effect of entrepreneurial marketing strategy on performance is not significant. As a result, the owner / manager of the furniture manufacturing SMEs using the guerrilla marketing strategy were found negative effect on the firm performance. Relationship marketing strategy is considered to be using this strategy, followed by niche marketing strategy is the most important determinant of marketing strategy. However, ambush marketing and viral marketing were found to have no significant impact on firm performance. This research contributes to the theoretical and practical knowledge systems by providing evidence of the relationship between niche marketing strategies and their impact on firm performance.